Aerosol Containment Box - Rao, Yellamanchali Sreenivas (Trans Indian Natl. Acad. Eng., 2020)
In the pandemic situation created by COVID-19, which is a fast spreading human-to-human transmittable disease, it is essential to protect health care providers. They are frontline warriors who fight this disease by treating patients and are most vulnerable to the same disease. In the current scenario, it is required to come up with innovative solutions to protect health care providers, such innovations should be made in to usable products with limited resources available due to lock down condition prevailing in the market and should be provided to them instantly. Main routes of infection of COVID-19 disease are, direct contact with objects that has virus on it and indirect contact by inhaling droplets emitted through sneezes and cough of patients. Healthcare providers can avoid direct contact with objects having virus by using proper PPE (Personal Protective Equipment). However, they are at risk of transmissions by microscopic aerosol particles consisting of the residual solid components of evaporated respiratory droplets, which are tiny enough (< 5 μm) to remain airborne for hours created by cough and sneeze. Authors have come with such a solution, called as ‘Aerosol Containment Box’ that act as barrier to safeguard health care providers from viral infection while performing medical procedures. It is made of transparent acrylic box, and covers COVID-19 patient from head up to chest. This box has to be placed on the body of the patient while he is being treated. This box is of low cost, can be made easily with limited resources and can be re-used after disinfection. This box is conceptualized, designed, manufactured, engineered and demonstrated within a record duration of 3 days. 100 nos of such boxes are made within 15 days and are distributed at various hospitals in Hyderabad. Engineering drawings and manufacturing process are documented and shared with outstation enthusiastic manufacturers.